BENEFITS AND CHALLENGES OF DMAIC METHODOLOGY IMPLEMENTATION IN SERVICE COMPANIES: AN EXPLORATORY STUDY - Subagyo, Ivan Evander; Saraswati, Dewi; Trilaksono, Teddy; Kusmulyono, Muhammad Setiawan (Universitas Brawijaya, Indonesia, 2020)
The DMAIC (Define, Measurement Analyze, Improve, Control) methodology of Six Sigma has been widely recognized as a breakthrough process improvement strategy for application among human resources that offers an impressive reduction in defects or errors in many business processes. Even though Six Sigma's DMAIC was predominantly applied in the manufacturing industry, recent studies have revealed that it has been implemented effectively in the service industry as well. This article aims to explore the benefits and the fundamental challenges of DMAIC implementation as a student's course project in five Indonesian service companies. An exploratory study was conducted to provide a clear understanding of DMAIC method implementation in service companies. A similar challenge, the lack of openness of the company, was found across cases. Several enhancements in company performance were identified, including improved customer satisfaction, reduction in delivery errors, and shorter waiting time. This research also highlighted the usage of some non-statistical tools and techniques that effectively contribute to each phase of the DMAIC method. Lastly, all five companies reported that these improvement projects offer positive benefits, including increased revenue and cost reduction.